(untitled) (KULT_online, 2011)
Since they combined printed words and images in letterpress for the first time, the incunabla printed by Pfister are considered to be milestones in book design. Indeed, they remain unique for the time being. Häussermann’s study on Pfister’s work points out the exceptional position of these early printed books, because their titles were very common in manuscript form, but not in further incunabla. In addition, she brings the functional use of woodcuts as book illustrations into focus by the comparison with illustrated manuscripts and the exposition of intrinsically medial specifics. For the woodcut cycles she traces the specific visual strategies employed to integrate the images, which predominantly consist of deliberately repeating and (re-)combining them. Furthermore these strategies play an important role in Pfister’s overall conception of his books: they contribute to the prints achieving their didactic goals.